DESIGN FOR MANUFACTURING (DFM) UNTUK MEMINIMASI BIAYA PRODUKSI DAN KUALITAS: STUDI KASUS PALLET BOX FABRICATION SECTION PT SAPTAINDRA SEJATI - Paduloh Sulthoni; Iskandar Zulkarnaen; Denny Wibisono; Andi Setiawan (Universitas Mercu Buana, 2017)
PT Saptaindra Sejati (SIS) is a company engaged in coal services, the company produces pallet boxes which is a fabrication product that is currently the demand is always there and desirable customers. The pallet uses the main raw materials such as iron elbows, iron pipes and iron plates. The production of pallet-making boxes is strongly influenced by the increase in material prices and the costs required for the process. One method of product improvement is approximated by design for manufacturing (DFM). This method is a design method that will be used for manufacturing minimum product requirement of components, printing and quality. PT Saptaindra Sejati in the fabrication section that makes pallet boxes focus on reducing components and improving production quality. Reduce components done by non-tobacco materials but still improve product quality. The production process can be improved by simplifying the production process. The main purpose of the process is the cost that can minimize production and quality. The result of DFM implementation to produce 1 pallet box will produce production cost up to 20,0% and quality cost up to 27,1%.